Early life exposure to vitamin D deficiency impairs molecular mechanisms that regulate liver cholesterol biosynthesis, energy metabolism, inflammation, and detoxification - Knuth, Megan M.; Xue, Jing; Elnagheeb, Marwa; Gharaibeh, Raad Z.; Schoenrock, Sarah A.; McRitchie, Susan; Brouwer, Cory; Sumner, Susan J.; Tarantino, Lisa; Valdar, William; Rector, R. Scott; Simon, Jeremy M.; et al. (Frontiers in Endocrinology, 2024)
Emerging data suggests liver disease may be initiated during development when there is high genome plasticity and the molecular pathways supporting liver function are being developed. Here, we leveraged our Collaborative Cross mouse model of developmental vitamin D deficiency (DVD) to investigate the role of DVD in dysregulating the molecular mechanisms underlying liver disease. We defined the effects on the adult liver transcriptome and metabolome and examined the role of epigenetic dysregulation. Given that the parental origin of the genome (POG) influences response to DVD, we used our established POG model [POG1-(CC011xCC001)F1 and POG2-(CC001xCC011)F1] to identify interindividual differences. We found that DVD altered the adult liver transcriptome, primarily downregulating genes controlling liver development, response to injury/infection (detoxification & inflammation), cholesterol biosynthesis, and energy production. In concordance with these transcriptional changes, we found decreased liver cell membrane-associated lipids (including cholesterol) and pentose phosphate pathway metabolites. Each POG also exhibited distinct responses. POG1 exhibited almost 2X more differentially expressed genes (DEGs) with effects indicative of increased energy utilization. This included upregulation of lipid and amino acid metabolism genes and increased intermediate lipid and amino acid metabolites, increased energy cofactors, and decreased energy substrates. POG2 exhibited broader downregulation of cholesterol biosynthesis genes with a metabolomics profile indicative of decreased energy utilization. Although DVD primarily caused loss of liver DNA methylation for both POGs, only one epimutation was shared, and POG2 had 6.5X more differentially methylated genes. Differential methylation was detected at DEGs regulating developmental processes such as amino acid transport (POG1) and cell growth & differentiation (e.g., Wnt & cadherin signaling, POG2). These findings implicate a novel role for maternal vitamin D in programming essential offspring liver functions that are dysregulated in liver disease. Importantly, impairment of these processes was not rescued by vitamin D treatment at weaning, suggesting these effects require preventative measures. Substantial differences in POG response to DVD demonstrate that the parental genomic context of exposure determines offspring susceptibility.